(untitled) (Journal of Environmental Science and Natural Resources, 2015)
SIDR had great impact on crop, livestock and fisheries at Pirojpur district in Barisal Division. To perform this study data were collected from the three selected village (south Shailkati, Hothkhali and Lahori) affected people by random sampling after selecting the study topic and area. SIDR also created a great impact on the production of different types of crop. Rice production was reduced to 7.5%, chili to 11.66% and vegetables to 10%. After SIDR the production of pulse was increased 21.67% due to increase in acreage in Pirojpur. From this study we found vegetables lands (58.33%) and fish in river (70.83%) were affected by the saline water than the rice (33.33%), fruit (9.16%) and fish in pond (24.16%) respectively. Due to the tidal surge and storm the cattle reduced to 18%, goats to 14%, buffalos to 21%, chickens to 10.09%, duck to 8.82%, Pigeons to 24%; that means majority of the poultry birds were reduced than the livestock. The food habit of the affected people was also changed. They now took more flour rather than rice. The scarcity of agricultural production created the reduction of food stock. Most of the respondents had no food stock. But the situation is better than close post SIDR period. Most of the cases they are adopting with the changing socio-economic conditions. DOI: http://dx.doi.org/10.3329/jesnr.v6i2.22084 J. Environ. Sci. & Natural Resources, 6(2): 25-30 2013